2005
DOI: 10.1021/ja053842c
|View full text |Cite
|
Sign up to set email alerts
|

Side-Chain Chiral Centers of Amino Acid and Helical-Screw Handedness of Its Peptides

Abstract: Both diastereomeric right-handed (P) and left-handed (M) 310-helices exist in homopeptides having twelve chiral centers at the side-chain bicyclic skeletons.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
26
0

Year Published

2005
2005
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 46 publications
(26 citation statements)
references
References 11 publications
0
26
0
Order By: Relevance
“…These results indicate that the chiral environment at the side chain is important for the control of the helical-screw direction of the peptide. 44) …”
mentioning
confidence: 99%
“…These results indicate that the chiral environment at the side chain is important for the control of the helical-screw direction of the peptide. 44) …”
mentioning
confidence: 99%
“…and C.T. ), [45] and the side-chain bis-substituted 1-aminocyclopentane-1-carboxylic acid recently reported by Tanaka, Suemune and their co-workers, [46,47] the latter being strictly related to c 3 diPhe as both residues are members of the class of side-chain disubstituted (on two vicinal carbons) 1-aminocycloalkane-1-carboxylic acids. It is also worth pointing out that the 3D-structural propensity of c 3 diPhe seems to be divergent, at least in part, from that of its side-chain positional isomer 1-amino-2,2-diphenylcyclopropane-1-carboxylic acid (or a,b-methanodiphenylalanine) (III) in the sense that the latter may easily explore the region of the f,y space (À708,708) where the g-turn conformation is usually found, [4,6,7] as recently demonstrated by two of us (A.I.J.…”
Section: Resultsmentioning
confidence: 85%
“…Tanaka et al have reported a highly efficient way to synthesis the optically active -amino acids with side chain chiral centre from (S,S)-cyclohex-4-ene-1,2-dicarboxylic acid 4 (Scheme 2) [21]. The acid (S,S)-4 was converted into a diiodide 5 by reduction and subsequent substitution with iodide.…”
Section: Synthesis Of -Amino Acids With Side Chain Chiral Centrementioning
confidence: 99%
“…Ph, Bn, H 2 C=CHCH 2 Scheme 1. , -Dialkyl--amino acids according to Ooi et al[21]. Reagents and conditions: (a) CsOH.H2O/ toluene -10 to 0°C; (b) 0.5 M citric acid, THF.…”
mentioning
confidence: 99%